LASSOing HRI: analyzing situation awareness in map-centric and video-centric interfaces - Drury, Jill L.; Keyes, Brenden; Yanco, Holly A. (2007 2nd ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2007)
Good situation awareness (SA) is especially necessary when robots and their operators are not collocated, such as in urban search and rescue (USAR). This paper compares how SA is attained in two systems: one that has an emphasis on video and another that has an emphasis on a three-dimensional map. We performed a within-subjects study with eight USAR domain experts. To analyze the utterances made by the participants, we developed a SA analysis technique, called LASSO, which includes five awareness categories: location, activities, surroundings, status, and overall mission. Using our analysis technique, we show that a map-centric interface is more effective in providing good location and status awareness while a video-centric interface is more effective in providing good surroundings and activities awareness.